Hyperoodon (Frasercetus) Moore 1968 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Hyperoodon (Frasercetus) Moore 1968 Hyperoodon (Frasercetus) Moore 1968, Fieldiana Zool., 53 (4): 274. Type Species: Hyperoodon (Frasercetus) planifrons Flower 1882 Species and subspecies: 2 species: Species Hyperoodon (Hyperoodon) ampullatus (Forster 1770) Species Hyperoodon (Frasercetus) planifrons Flower 1882 Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Cetacea, pp. 723-743 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 740, DOI: 10.5281/zenodo.7316519